A relativização da coisa julgada e a ação rescisória - Lemos, Denise Cerqueira (2013)
This present study aims to analyze how to rescind final decisions incompatible with constitutional norms. The sentence, even if res judicata, whether based on law later declared unconstitutional, will be null and void and may be to rescinding at any time since the unconstitutional acts ever to validate by lapse of time, because the addiction would be contained within incurable. Having such remedies applicable bringing action for rescission or declaratory action for invalidity.